Effects of Instructions, Assistance, Narrative, Competition, Challenge, and Age on Performances in Digital Learning Games - Leuchter, Inbal; Kurtz, Gila (International Journal of Advanced Corporate Learning (iJAC), 2022)
Studies have shown that digital game-based learning (DGBL) can stimulate learners and increase motivation. However, in order to accomplish these goals, we must understand the role and impact of the game elements. This study aimed to examine the effects of four-game elements on player performance: Instructions and assistance, narrative, Competition, and Challenge. An additional factor examined was players’ age. The data was collected using BIG DATA from the game platform, which recorded the scores of 3,281 users across nine different games, during the period 2015-2020. Users played as part of their visit to ’Musa’, a multidisciplinary museum of local cultural materials in Tel-Aviv, either in ’Family’ game mode or in ’Group’ mode. According to the results of our study, players performed better on ’Group’ games. In addition, players’ performances improved when narrative depth was significant and the play area was smaller. Separating our data into two groups led to additional results: players in ’Family’ mode performed better when the game instructions included a video, while in ’Group’ modes participants performed better when a human guide was available to some extent. The results of this study and their implications can assist educators and game designers in planning more accurate and effective learning games.